Implementasi Gerakan Literasi Sekolah Dan Pembelajaran Mendalam Sebagai Upaya Mendukung Kemampuan Literasi Membaca Peserta Didik Di Sekolah Dasar Negeri 61 Manado - Ndolu, Sumardi W.; Tahulending, Meylani T.; Mudjito, Delfiana; Sasior, Fonita K.; Saflembolo, Feberina (Peneliti.net, 2025)
This study aims to describe the implementation of the School Literacy Movement (GLS) and deep learning as efforts to improve reading literacy skills among elementary school students. The research employed a descriptive qualitative method using observation, interviews, and documentation as data collection techniques. The findings show that the implementation of GLS at SD Negeri 61 Manado has been carried out through a 15-minute daily reading activity, the provision of reading corners, and the use of literacy journals. Meanwhile, deep learning is implemented through text analysis and reflective discussions. The integration of GLS and deep learning positively impacts students’ motivation to read, their ability to identify main ideas, draw conclusions from texts, and participate actively in class discussions. These findings emphasize that the implementation of GLS and deep learning must be conducted consistently and sustainably to strengthen elementary students’ reading literacy